IMPLEMENTATION OF BUILDING SUPPORT PROGRAM FOR SELF-HELP HOUSING / BEDA HOME FOR PEOPLE IN BUO VILLAGE, SOUTH LOLODA SUB-DISTRICT, HALMAHERA BARAT DISTRICT, NORTH MALUKU PROVINCE - TALIAWO, ROKI; RUMAPEA, PATAR; DENGO, SALMIN (Sam Ratulangi University, 2018)
Implementation of self-help stimulant assistance for Buo village community, Loloda sub district, WestHalmahera district, North Maluku province. This research uses qualitative method (Observation, In-depthInterview (Indepeth Interview), Documentation). Informant of this research as many as 10 people, 2employees of Housing and residential area, 1 contractor BSPS, 3 village government, 4 Communityreceiving BSPS. The collecting technique used is interview (interview), sedangkat data analysis is donewith qualitative analysis technique method Based on the results of this study was drawn Conclusion:Implementation of policy is the activity seen after issued a legitimate directives of a policy that includesefforts to manage inputs to produce output or outcome for the community. And the aid of self-help housingstimulant of Self-Housing Stimulant Support hereinafter abbreviated as BSPS is government facilitation inthe form of stimulant aid for development / improvement of house quality to Low Income Society. With theRegulation of the Minister of Public Works and People's Housing of the Republic of Indonesia Number 39/ PRT / M / 2015 On Amendment To The Regulation of Minister of Public Housing No. 06 Year 2013 Aboutthe Implementation Guidance for Self-Helping Housing Stimulants, the community is given the right toobtain adequate housing left.Keywords: Implemtation, Service and housing